Evaluation of uncertainties in in situ and ex situ gamma measurements on land areas with low contamination levels - Rostron, Peter D; Heathcote, John A; Ramsey, Michael H (Journal of radiological protection, 2015)
Previous work on the characterisation of land areas with moderate contamination levels showed that in situ measurements made with a gamma detector can achieve lower levels of the random component of uncertainty than laboratory measurements of extracted samples. This was found when the variance caused by small-scale lateral heterogeneity of contaminants was included in the uncertainty estimation. The present paper documents the results of applying the same techniques of uncertainty estimation to an area with contamination levels that were lower by a factor of 10. If the same counting times were used, it would be expected that both measurement types would be affected by higher levels of random uncertainty in the individual measurements because of increased uncertainty from counting statistics and other factors such as interpretation of gamma spectra. However, when uncertainty due to sampling was included, it was found that both measurements methods were subject to similar combined uncertainties at individual locations. Using an assumption of the depth distributions of radionuclides that was supported by ex situ measurements, in situ measurements were able to produce averaging estimates with an approximate reduction of 50% in the standard error on the mean at ~50% of the cost of the ex situ measurements.